Investigation of organic–inorganic hybrid perovskite solar cells based on Al2O3 nanorods. (1st September 2017) - Ma, Li; Liu, Ping; Wu, Xiaojie; Li, Haitao; Jiang, Yaxiao; Tu, Limin; Chen, Yongsheng; Lu, Jingxiao; Yang, Shi-e
Highlights: The Al2 O3 nanorods (NRs) -based perovskite solar cells is simulated. The effects of the packing density, length and porosity of NRs are investigated. An optimal length of 450 nm for Al2 O3 NRs is obtained with efficiency over 20%. Abstract: Organic–inorganic hybrid perovskite solar cells have made great breakthroughs in the past few years, and spurred researchers to develop and experiment a variety of new architectures. One-dimensional nanostructures are naturally introduced in solar cells, because of their excellent charge transport properties and open-pore structure. However, the performances of these solar cells are inferior to their mesoporous counterparts, suggesting that some unique mechanisms maybe held behind devices operation. Here, a three-dimensional optical model combined with a two-dimensional axisymmetric semiconductor model is applied to investigate the influence of the architectural design of scaffolds on the properties of perovskite solar cells based on Al2 O3 nanorod arrays. Simulation results show a great dependence of device performance on the density, length and porosity of Al2 O3 nanorods, which decided the electron field distribution and carrier recombination loss inside the cells. Strikingly, an optimal length of 450 nm for Al2 O3 nanorods is obtained for the perovskite solar cells with efficiency over 20% at porosity of 0.7. The results obtained have some guidance function on the fabrication of high efficiency PSCs based on nanorods.